PENGARUH CAREER MANAGEMENT, CAREER ADAPTABILITY TERHADAP EMPLOYEE ENGAGEMENT DENGAN JOB SECURITY SEBAGAI VARIABEL MODERASI: STUDI PADA PT ADARO INDONESIA SITE KALIMANTAN - Endang Daris; Hastin Umi Anisah; Mayasari Dewi (CV. Publikasi Indonesia, 2021)
This research aims to determine and analyze the effect of career management and career adaptability on the employee engagement with job security as a moderating variable for the workers of PT Adaro Indonesia of Kelanis site. This causality research carried out based on quantitative approach. Data obtained using questionnaires selected by the quota sampling technique. The samples were selected on the specified criteria, namely from the level staff up to Manager with minimum working period of 3 years. Data were analyzed using the Structural Equation Modeling (SEM) equation with the Partial Least Square (PLS) approach. The results showed that separately career management, career adaptability and job security had a significant effect on employee involvement. Hypothesis test result also indicate the influence of career management and career adaptability to the employee engagement with job security as moderating predictor.